Effect of LH-RHa Injection trough W/O/W LG (C-14) Emulsion on Gonad Development of Catfish (Pangasious hypophthalmus) - Potalangi, N.; Toelihere, M.; Junior, M. Zairin; Supriyono, Eddy (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The objective of this research was to study the effect of LHRHa gonad maturity in broodstock of P. hypophthalmus through W/O/W LG (C-14) emulsion injection. The treatments consisted of control (A), 50 µg/kg fish wight (B), and 100 µg/kg fish weight (C), with five replications of each. Fish weight at the beginning of experiment was 2.0 kg/individual. The result showed that LHRHa in W/O/W emulsion had positive effect on egg maturation. This was shown by the value of average of eggs diameter. The maximum size of egg diameter for fish 701.52 ± 17.56 µm. The size of eggs was more homogenous in group B than those of group C and A. it was concluded that injection of LHRHa in W/O/W LG (C-14) emulsion if effective in promoting gonad maturation and oocyte development in the catfish